System Analysis of The Parallel Execution Problem - Тевяшев, А. Д.; Гольдінер, Д. І. (My University, 2019)
The article studies the prerequisites for the appearance and dissemination of the approach to optimizing the execution of program code through the simultaneous execution in several threads, analyzes the problem of parallel computing, identifies factors affecting the feasibility and effectiveness of the implementation of the architectural solution for multi-threaded program execution. Also, the problems that may arise during the implementation of optimization are considered. The main advantages and disadvantages of using the Go programming language for implementing parallel execution of a software product are considered.
Keywords: parallelism; concurrency; execution thread; source code; memory allocation; optimization; multithreating; programming